PERAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN - Fitrah, Muh. (Jurnal Penjaminan Mutu, 2017)
This writing has main purpose that is to know head masterâs role in improving educational quality, leadership, duty, and headmasterâs role in improving educational quality, leardership, duty, and headmasterâs role in order to produce process and product of quality education. Educational quality is our hope in facing strict life exchange in several sectors especially in education sectors for better future. For the sake of making educational quality, this needs role of leaders in educational institutes. One of them is headmaster because it is the pioneer is moving all changes to go to educational quality. Headmasterâs duty is not only leading ceremony, waiting incoming letter to be signed but also making a good quality of education in school. Specifically headmasterâs role in improving quality of education are doing monitoring, evaluating continually toward seccessful program determined, planning and arranging word plan agreed with improving needs of educational quality which orients on schoolâs mission, making intensive commumication with teachers, students, studentâs parents and society.